Do Audit Fees and Characteristics of CEO Decrease Audit Delay in Mandatory IFRS Adoption? - Mawardi, Rizal; Lanjarsih, Laela (Binus Business Review, 2020)
The research examined characteristics of CEO and audit fees on audit delay related to changes in mandatory IFRS adoption. In the setting, gender and audit fees were the level of risk tolerance, overconfidence, diligence, and monitoring intensity. As a result, these individual differences were likely to be reflected in audit delay in financial reporting decisions. Using firm data levels between 2008 and 2016 with multivariate regression, the research provided empirical evidence supporting the hypothesis that the characteristics of CEO and audit fees were the determinants of audit delay. There are several findings. First, the financial expertise of the CEO has more significant percentages in mandatory IFRS adoption than voluntary IFRS adoption. It is associated with a shorter delay. Second, having a female CEO and appointing a female and minority CEO will increase the likelihood that firms will issue financial reports more timely. Third, higher audit fees in mandatory than voluntary IFRS adoption can decrease audit delay.